2011
DOI: 10.1586/eci.10.98
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and cardiovascular disease: prediction and potential for therapeutic intervention

Abstract: Patients with systemic lupus erythematosus have a significantly increased risk of cardiovascular events due to atherosclerosis. Traditional cardiac risk factors cannot fully explain this increased risk. Recent evidence strongly suggests that atherosclerotic plaque is largely driven by inflammation and an active immunological response, in contrast to the long-held belief that plaque is a passive accumulation of lipids in the arterial wall. Current approaches to the prevention of atherosclerosis in systemic lupu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 200 publications
(229 reference statements)
2
74
0
Order By: Relevance
“…However, this should not have biased our results, as lupus-like illness is associated with accelerated, but not with reduced, atherosclerosis. 42 The lower IMT in carriers of NOX2 deficiency was another important evidence in favor of the reduced atherosclerotic burden in subjects with impaired ROS production. Thus, IMT is a noninvasive diagnostic measure of atherosclerosis that correlates with histology and predicts cardiovascular events, including myocardial infarction and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, this should not have biased our results, as lupus-like illness is associated with accelerated, but not with reduced, atherosclerosis. 42 The lower IMT in carriers of NOX2 deficiency was another important evidence in favor of the reduced atherosclerotic burden in subjects with impaired ROS production. Thus, IMT is a noninvasive diagnostic measure of atherosclerosis that correlates with histology and predicts cardiovascular events, including myocardial infarction and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients with SLE show a significant increased incidence of atherosclerosis and cardiovascular events when compared with healthy individuals. 64 The T1 IFN IFN-ÎČ is frequently used as a treatment of patients with relapsing remitting multiple sclerosis where it surprisingly has opposite effects on cerebral endothelial activation when compared with the peripheral endothelium. 65 About cell recruitment to the plaque, a recent in vivo study showed that T1 IFNs increased cell recruitment to atherosclerotic lesions in a CCL5-dependent manner.…”
Section: Ifns In Endothelial Activation and Cell Recruitmentmentioning
confidence: 99%
“…It is well known that the cardiovascular disease (CVD) morbidity and mortality of patients with SLE is substantially increased as compared to the general population [1][2][3]. Moreover, CVD occurs at a younger age in SLE patients than in the general population [3,4].…”
Section: Introductionmentioning
confidence: 99%